(untitled) (Archive of Conferences, 2020)
Zulfiya is one of the greatest representatives of Uzbek poetry of the 20th century. He left an important mark on the literature of the time with his deep philosophical, complex aspects of life, his unique lyrical works, epics and fiery publicist works that reflected the unique colors and emotions of man. Zulfiya’s poetry is an intellectual and psychological poetry formed by a combination of deep thought and passion. The poet draws a flow of emotions, a scene of experience, a sharp dramatic state, as well as the most dramatic collisions. Zulfiya’s poetry is spiritually rich, spiritually refreshing, and courageous. It covers a wide range of time and space. Reality and human destiny are reflected in harmony with yesterday, today and tomorrow. This is the significance and stability of the expression of the motives of "destiny", "people close to the heart", and "future" in the poet’s lyrics. The high spirit in the poet’s work, along with the tone of happiness, is due to the fact that he does not burn in the direction of tragedy, because he goes through the analysis of reality, time, man in a broad and holistic, with all its complexity.